Ilex calcicola (Aquifoliaceae), a new species from a limestone area of Guangxi, China - Xu, Kewang; Shi, Xianggang; Fan, Qiang; Xu, Weibin; Liao, Wenbo (Phytotaxa, 2017)
Ilex calcicola (Aquifoliaceae), a new species from western Guangxi, China, is described, illustrated, and compared to two morphologically similar species: I. mamillata and I. wuana. The scanning electron micrographs of pollen grains and stomata of this new species are also showed in the plate. I. calcicola is currently known only from the limestone hills in western Guangxi.